Modulation of Lipid Profile and Lipoprotein Subfractions in Overweight/Obese Women at Risk of Cardiovascular Diseases through the Consumption of Apple/Berry Juice - Marta Habanova; Maria Holovicova; Hana Scepankova; Marta Lorkova; Jan Gazo; Martina Gazarova; Carlos A. Pinto; Jorge A. Saraiva; Leticia M. Estevinho (MDPI AG, 2022)
Polyphenol-rich foods protect the cellular systems of the human body from oxidative damage, thereby reducing the risk of chronic diseases such as cardiovascular disease (CVD). We investigated the effect of phenolic-rich apple/berry juice (chokeberry, blueberry, and cranberry) on lipidemic profiles in overweight/obese women. The 6 week single-arm pre-post intervention study involved 20 women (mean age 52.95 ± 5.8 years, body mass index ≥25 kg/m2, and ≥1 CVD risk factors) consuming 300 mL/day of the apple/berry juice. Lipid profile, low-density lipoprotein (LDL) subfractions assessed using Lipoprint® electrophoresis, and other parameters related to cardiovascular risk (C-reactive protein, glucose, blood pressure) were analyzed before and again after the intervention in the monitored group of women. High-density lipoprotein cholesterol (HDL-C) increased from 1.30 ± 0.29 to 1.55 ± 0.32, magnesium from 0.85 ± 0.03 to 0.90 ± 0.05, and total antioxidant status from 1.68 ± 0.08 to 1.81 ± 0.10. The LDL/HDL ratio significantly decreased from 3.40 ± 0.99 to 2.66 ± 0.63 mmol/L, and the glucose from 5.50 ± 0.72 to 5.24 ± 0.74 mmol/L. However, the hs-CRP did not change significantly. Women with atherogenic subfractions LDL3-7 at baseline (n = 6) showed a significant reduction from 0.45 ± 0.19 to 0.09 ± 0.07 mmol/L. Overweight/obese women may benefit from apple/berry juice as part of a healthy lifestyle to improve their lipid profile, and thus, contribute to cardiovascular health.